Proceedings of the 11th Working Conference on Mining Software Repositories 2014
DOI: 10.1145/2597073.2597117
|View full text |Cite
|
Sign up to set email alerts
|

Security and emotion: sentiment analysis of security discussions on GitHub

Abstract: Application security is becoming increasingly prevalent during software and especially web application development. Consequently, countermeasures are continuously being discussed and built into applications, with the goal of reducing the risk that unauthorized code will be able to access, steal, modify, or delete sensitive data. In this paper we gauged the presence and atmosphere surrounding security-related discussions on GitHub, as mined from discussions around commits and pull requests. First, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 8 publications
5
105
0
Order By: Relevance
“…This three metrics have been used by other researchers, i.e., politeness [23] and [24], sentiment [25] and [26], and emotion [9].…”
Section: Introductionmentioning
confidence: 99%
“…This three metrics have been used by other researchers, i.e., politeness [23] and [24], sentiment [25] and [26], and emotion [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sentiment polarity analysis has been recently applied in the software engineering context to study commit comments in GitHub [9], GitHub discussions related to security [10], productivity in Jira issue resolution [11], activity of contributors in Gentoo [12] and evolution of developers' sentiments in the openSUSE Factory [13]. It has also been suggested when assessing technical candidates on the social web [14].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, all the aforementioned software engineering studies reuse the existing sentiment polarity tools, e.g., Guzman et al [15], [9] and Rousinopoulos et al [13] use NLTK, while Garcia et al [12], Pletea et al [10] and Ortu et al [11] opted for SentiStrength. While the reuse of the existing tools facilitated the application of the sentiment polarity analysis techniques in the software engineering domain, it also introduced a commonly recognized threat to validity of the results obtained: those tools have been trained on nonsoftware engineering related texts such as movie reviews or product reviews and might misidentify (or fail to identify) polarity of a sentiment in a software engineering artefact such as a commit comment [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…The information needs solely identified by the authors are confirmed with the managers by presenting them the information needs along with the example analysts' comments where such an information is asked. Comment annotation using keywords-based approach: Ground truth for every information need is established using a keyword-based approach [52]. A list of keywords corresponding to each information need is prepared iteratively.…”
Section: Ground Truthmentioning
confidence: 99%